Peripheral Inflammatory Biomarkers of Methamphetamine Withdrawal Patients Based on the Neuro-Inflammation Hypothesis: The Possible Improvement Effect of Exercise - Wang, Jingsong; Lu, Chunxia; Zheng, Lan; Zhang, Jun (Frontiers in Psychiatry, 2021)
Neuroinflammation induces neurotoxicity and addiction among methamphetamine (MA) abusers. Based on the neuroinflammation hypothesis, this study aims to investigate how exercise influences the craving of patients in MA withdrawal, and explore the mechanism of peripheral inflammation. A total of 90 patients in MA withdrawal were recruited. No difference was noted in the number of years of drug use and the frequency of drug use among patients, and the withdrawal time was within 2 months. The subjects were grouped based on the degree of craving induced by the cues :non-craving control group (NCC group), craving control group (CC group), and craving exercise group (CE group). The CE group was subjected to aerobic combined resistance training. Then, the ELISA method was used to detect plasma IL-6, TNF-α, and IL-1β concentrations; Visual Analogue Scale (VAS) measurement of cue-induced cravings under Virtual Reality (VR) exposure (VR-VAS) and the Desires for Drug Questionnaire (DDQ) were used to assess cravings. Consequently, plasma IL-6, TNF-α, IL-1β, levels, and the VR-VAS and DDQ scores of MA withdrawal patients were significantly reduced after exercise. Besides, the scores of VR-VAS positively correlated with the plasma concentrations of IL-6, TNF-α, and IL-1β. This study confirmed that plasma IL-6, TNF-α, and IL-1β can be used as biomarkers of peripheral inflammation among MA withdrawal patients in predicting the degree of craving. At the same time, eight weeks of incremental load aerobic combined with resistance training reduces peripheral inflammation and significantly reduces the level of craving for MA.